Concerning the Madrid Lecture: The Equivocal Character of Pavlov’s Reflexological Objectivism and its Influence on the Distorted Concept of the Physiology-Psychology Relationship - Bautista Fuentes, Juan (The Spanish Journal of Psychology, 2003)
The aim of this study is to bring to light and make clear the characteristic equivoque Pavlov made when he conceived the neurophysiological circuit involved in conditionedbehavior as if this circuit contained or reduced, in its own terms, such behavior. I also wish to point out how this interpretation implies a distorted concept of the relationships between neurophysiology and behavior. As an alternative, it is proposed that behavior, which is always operant behavior, is not at all reducible to its neurophysiological ingredients, but instead acts like an arrow-head for adaptation that, in turn, confers a subordinate function to the neurophysiological ingredients involved. To make this evident, behavior is considered an operant organic activity that takes place in an environment of “remote co-present” texture, and different from its neurophysiological ingredients, which take place within the context of spatial contiguity relationships.